2021
DOI: 10.4314/jasem.v25i5.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Malaria Parasitaemia among the Residents of Abuja Municipal Area Council (AMAC), FCT, Abuja, Nigeria

Abstract: Malaria intensity in both Urban and Rural areas of Nigeria is of Public Health importance. This study was conducted to assess the malaria parasitaemia among the residence of Abuja Municipal Area Council, FCT, in order to provide epidemiological data on malaria in the council for effective management program. A total of 200 residence within the range of 2-50 years were sampled for malaria parasitaemia using thick and thin film smears. A capillary blood sample was collected from each of the residence using finge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…It showed that the degree of anemia varies in children varied depending on the mother’s job level and the parents’ educational background. 18 …”
Section: Resultsmentioning
confidence: 99%
“…It showed that the degree of anemia varies in children varied depending on the mother’s job level and the parents’ educational background. 18 …”
Section: Resultsmentioning
confidence: 99%